2018
DOI: 10.1177/1744806918787427
|View full text |Cite
|
Sign up to set email alerts
|

ATF2, but not ATF3, participates in the maintenance of nerve injury-induced tactile allodynia and thermal hyperalgesia

Abstract: Transcription factors are proteins that modulate the transcriptional rate of target genes in the nucleus in response to extracellular or cytoplasmic signals. Activating transcription factors 2 (ATF2) and 3 (ATF3) respond to environmental signals and maintain cellular homeostasis. There is evidence that inflammation and nerve injury modulate ATF2 and ATF3 expression. However, the function of these transcription factors in pain is unknown. The purpose of this study was to investigate the contribution of ATF2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…In consent with our results, it has been documented that high expression of Smurf1 was observed after SCI in rats 25 . The up‐regulation of ATF2 expression has also been reported in injured L5/6 dorsal root ganglia and spinal cord after nerve injury 26 . Our results from the dual‐luciferase reporter gene assay depicted that Smurf1 was a putative target gene of miR‐125b.…”
Section: Discussionsupporting
confidence: 90%
“…In consent with our results, it has been documented that high expression of Smurf1 was observed after SCI in rats 25 . The up‐regulation of ATF2 expression has also been reported in injured L5/6 dorsal root ganglia and spinal cord after nerve injury 26 . Our results from the dual‐luciferase reporter gene assay depicted that Smurf1 was a putative target gene of miR‐125b.…”
Section: Discussionsupporting
confidence: 90%
“…Collectively, this report suggests that ATF3, a stress-inducible gene, modulated the profile expression of p-PKCε and Bcl- XL , which was correlated with the development of neuropathic behavior. Paradoxically, recent reports have indicated that ATF2 – but not ATF3 – is responsible for neuropathic pain 35. Our previous studies reported ATF3 preferentially on small-diameter DRG neurons,11,12 and in those cases, we suggested that the role of ATF3 is more convincing in small-diameter neuropathy.…”
Section: Discussionmentioning
confidence: 54%
“…The gene Atf3, coding for the transcription factor ATF3, is regarded as a marker of neuronal injury, but also of neuronal regeneration [90,91]. Previous studies have also found upregulation of Atf3 in both DRG and SC in males [92]. The effect of male-only upregulation of Atf3 and Reg3b in SC on behavioural sex difference remains to be studied.…”
Section: Plasticitymentioning
confidence: 99%